Acute disseminated encephalomyelitis post-SARS-COV-2 vaccination with Chadox1 nCov-19 (AZD1222) – A rare case report - Sivji, Meghna; MV, Vidya; Pratap, Thara; Abdul Jalal, Muhammed Jasim (Eastern Journal of Medical Sciences, 2022)
Background: Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the CNS, characterized by fulminant multifocal neurologic injury and distinct neuropathologic findings.Case Report: We report a case of a forty-nine-year-old female who presented with progressive weakness of right side of the body of one-week duration. Clinical, laboratory and radiological features favored demyelination. There was temporal association with taking SARS COV 2 vaccination (ChAdOx1 n cov -19 (AZD1222)). She was treated with a course of steroids and made a good recovery.Conclusion: To our knowledge this is a rare case of ADEM noticed after ChAdOx1 nCoV-19 vaccine (AZD1222).